The opinions of mental health professionals regarding criminal responsibility and treatment of psychopathic offenders - Whitmore, Laura-Ashley (2016)
The criminal responsibility and treatment of psychopathic offenders is continuously debated, however, there is limited research investigating the opinions of mental health professionals towards psychopathic offenders. This study investigated whether psychologists and psychiatrists thought psychopaths should be held criminally responsible, if psychopathy is treatable and where treatment ought to be received (prison or hospital). The results showed psychologists and psychiatrists thought psychopaths should be criminally responsible, psychopathy is treatable and psychopathic offenders can be rehabilitated. There was a divide in opinion regarding where treatment should be received; some felt treatment should occur in prison whereas others should psychopathic offenders should be transferred to a secure hospital for treatment.